Hydrogen Based Compounds as Energetic Catalysts for Liquid Rocket Engines: Implications and Applications - Ray, Triparna; Malhotra, Vinayak (Asian Review of Mechanical Engineering, 2021)
In the current scenario of space propulsion, liquid propellants have significantly proved useful in the upper stage rocket engines. Over the past couple decades, the world had inclined positively towards cryogenic fuel(s) viz., liquid oxygen and liquid hydrogen due to their high specific impulse. A higher specific impulse implies lower duration to achieve design cruise velocity for a given rocket initial and instantaneous mass. Liquid hydrogen and liquid oxygen as fuel and oxidizer can generate one of the highest enthalpy release in combustion, producing a specific impulse of up to 450 seconds at an effective exhaust velocity of 4.4 kilometres per second. Whereas, selected disadvantages are encountered in the form of storage and production. This indicates overdependence on cryogenic propellants and has necessitated the active research effort for better alternatives. As an interesting alternative, the combination of Dinitrogen Tetroxide (N2O4) and Monomethyl Hydrazine (MMH) have been used for many space applications owing to an extreme storage stability and hypergolic nature. Present study aims to express the effect of hydrogen-based compounds on the rocket performance. Four distinctive compounds from two groups of hydrogen-based compounds are tested with the varying oxidizer and fuel proportions to obtain a new, cost-effective and user-friendly composition that can be prepared at room temperature. The investigation attempt and explains the effect of hydrogen based energetic propellants using N2O4 and MMH as the base composition for upper stage performance. The work is motivated by the need of efficient space operations with attractive propulsive alternatives to minimize over-dependence on cryogenics, which will ultimately result in cost effectiveness. Various energetic materials were tested with the base composition by using standard NASA-CEA complex chemical equilibrium model. The performance was evaluated in terms of variation in specific impulse and characteristic velocity both of which are significant parameters. To, validate the practical utility, the role of chamber pressure, supersonic area ratio and optimal Oxidizer to fuel ratio (O/F) was determined. The work led to two interesting findings, a composition of beryllium hydride with base composition for high performance of rockets and the negative impact of hydrogen on liquid propellants.